The use of micro-simulation in determining the capacity of a roundabout with a multi-channel pedestrian flow - Tollazzi, Tomaž (Strojniški vestnik, 2008)
The main purpose of this paper is to analyse the influence of the multi-channel pedestrian flow on the capacity of the one-lane roundabout, using discrete simulation methods. The proposed model is based on the theory of the expected time void between the units of pedestrian traffic flow, which have the priority when crossing the arm of the roundabout. The proposed model represents an upgrade of the previous research in the field of modelling traffic flows in the one-lane roundabout. While the previous model of the pedestrian crossing is handled as the single-channel system in which the pedestrians arrive randomly from one side of the pedestrian crossing only, the proposed model deals with the multi-channel system in which the pedestrians arrive randomly from both sides of the pedestrian crossing. In thi sway the mathematical model can better illustrate the real conditions. The previous model considers only the disturbances of entry traffic flow of motorised vehicles caused by the pedestrian flow crossing the roundabout arm. The proposed model considers the disturbances caused by the circular traffic flow of motorised vehicles as well. A simulation analysis has been conducted on the roundabout at Koroška Street in Maribor, in which the counting of the motorised traffic flow and the pedestrian flow has been performed in the morning peek hour. The results of the analysis have indicated a high reserve of the capacity for pedestrians who arrive from the left and right sides of the roundabout with regard to motorised vehicles in the analysed arm of the roundabout. The real reserve of the capacity would otherwise be smaller in case of enlargement of the motorised vehicle flow in the future. Nevertheless it would be high enough for an undisturbed traffic flow of motorised vehicles through the roundabout to be possible. The presented methodology represents a practicable and adaptable tool for planning the roundabout capacity in practice and for the sensitivity analysis of individual variables on the throughput capacity of the roundabout.
Keywords: promet; krožišča; pešci; prehodi za pešce; modeli